The Impact of Utilizing Artificial Intelligence In Independent Curriculum-Based Learning - Mutiara Ningtyas, Pranistya Dwi Ayu; Haris, Ikhfan (Jayapangus Press, 2024)
The 5.0 era is a milestone in all forms of technological development in various fields. The emergence of a system that provides wide access and is able to easily solve every problem with the right solution is called artificial intelligence. The system has now entered the scope of education. Its use is in the administration and implementation of learning, by providing convenience for teachers in presenting innovative material content. Artificial intelligence (AI) has a significant impact on the implementation of independent curriculum-based learning. The curriculum emphasizes student-centered learning, so the use of AI can be an alternative to developing interesting and fun teaching methods and media so that students get a meaningful learning experience. This research aims to determine the impact of the use of AI on independent curriculum-based learning. Then, using a descriptive qualitative research method with literature review analysis. Furthermore, the results of the research are that artificial intelligence is able to improve student understanding through more interactive learning, because in the implementation of learning using various methods, models, and media adapted to student needs. The impact of the use of artificial intelligence (AI) as a form of technological advancement in learning includes several important aspects, namely 1) in learning using artificial intelligence (AI) to improve learning personalization and 2) the use of artificial intelligence (AI) is in line with independent curriculum-based learning that carries the concept of independent learning. Thus, artificial intelligence (AI) can be used as a teacher's learning assistant to strengthen and develop the preparation of effective teaching tools.